Penguatan Komunikasi Pariwisata Air di Dermaga Pantai Menye Danau Laut Tawar Takengon - Deddy Satria M; Fitria Akmal; Syifa Urrahmah; Nurhayati Nurhayati; Al Chaidar (Jurnal Solusi Masyarakat (JSM), 2026)
The rapid development of water tourism at Menye Beach Pier, Lake Lut Tawar, Takengon, has not been fully matched by optimal public communication and safety protocols. This community service program, conducted by the Department of Communication Science at Universitas Malikussaleh on June 26, 2026, aimed to strengthen the water tourism communication capacity of local tourism awareness groups (Pokdarwis) and pier operators. Employing a Participatory Action Research (PAR) approach, the program progressed through four stages: diagnosis, planning, action, and evaluation. Interventions focused on hospitality communication training, safety briefing simulations, the installation of intuitive visual safety signage, and the development of local culture-based storytelling narratives. The results demonstrated a significant enhancement in operators' interpersonal skills, particularly in convincingly delivering safety protocols to visitors. Furthermore, the newly installed visual media improved safety awareness, while cultural storytelling added value to the tourist experience. The program concluded with the handover of a Standard Operating Guideline for pier communication to ensure long-term sustainability. This initiative successfully fostered a safer, more hospitable, and professional water tourism environment in Central Aceh.